Diet composition and reproductive biology of spineless cuttlefish Sepiella inermis (Orbigny, 1848) from Ratnagiri (Arabian Sea, North-west coast of India) - Mahadwala, P. L.; Nirmale, V H; Metar, S. Y.; Bhosale, B P; R. A. Pawar; Chogale, N D (Indian Journal of Fisheries, 2023)
In the present study, we investigated some biological aspects of the spineless cuttlefish, Sepiella inermis (Orbigny, 1848) along the Ratnagiri coast of Maharashtra, India. A study on diet composition and reproductive biology of the species was carried out. Dorsal mantle length (DML) ranged from 35.9 to 93.3 mm for males and 29.3 to 98 mm for females. Feeding intensity was noted to be low during most of the study period. S. inermis was found to have a protracted spawning season. The overall male: female ratio was 1:1.02 during the study period. The average fecundity was found to be 358 eggs. Length at sexual maturity was estimated to be 42 mm and 53 mm for males and females respectively. The information obtained from the study will help the fishery agencies to formulate management measures in sustaining the landings of S. inermis in the region. Keywords: Biological studies, Cephalopods, Maharashtra, Ratnagiri coast, Sepiella inermis, Spineless cuttlefish